Simplify. (2x^-3y^4)^3 (6x^8y^-15) (4x^2y)/(3xy)^2 (8x^-9y^7)

1 Answer | Add Yours

embizze's profile pic

embizze | High School Teacher | (Level 2) Educator Emeritus

Posted on

Simplify `((2x^-3y^4)^3 (6x^8y^-15) (4x^2y))/((3xy)^2 (8x^-9y^7))`:

First eliminate the parentheses using `(ab)^x=a^xb^x`


Now use `a^x*a^y=a^(x+y)` in both numerator and denominator:



Now use `a^x/a^y=a^(x-y)` :



Now use `a^(-x)=1/a^x`


Which is fully simplified.

We’ve answered 319,863 questions. We can answer yours, too.

Ask a question